Beyond despair: Leveraging ecosystem restoration for psychosocial resilience - Carter S. Smith; Elizabeth A. DeMattia; Elizabeth Albright; Abigail F. Bromberger; Olivia G. Hayward; India J. Mackinson; Sydney A. Mantell; Brian G. McAdoo; Dominic McAfee; Aurora McCollum; Avery B. Paxton; Anne Roderer; et al. (Proceedings of the National Academy of Sciences, 2025)
Ecosystem restoration has historically been viewed as an ecological endeavor, but restoration possesses significant, yet largely untapped, potential as a catalyst for personal and social transformation. We highlight the opportunity for restoration to enhance community resilience by increasing agency and collective action and countering the pervasive perception that we are powerless witnesses to environmental decline. In this perspective, we take a “bright spots” approach and highlight successful examples of ecosystem restoration that have helped to nurture a sense of place, foster optimism, and cultivate stronger and more diverse social networks. These three individual- and community-level capacities have the potential to lead to increased psychosocial resilience, which is a key component of community resilience. Our aim is to spark discussion and research to better understand how we can transform restoration from a largely technical endeavor to a practice and process through which human–nature relationships are infused with deliberate meaning and human well-being is improved. With current calls to upscale and technologize restoration to meet sustainable development goals, we cannot lose sight of the value of community-engaged ecosystem restoration as a strategy with great potential for psychosocial benefits.